Isolation, Molecular Characterisation, and Pathogenicity Analysis of a Novel Recombinant ALV‐J Strain Isolated From Chinese Hetian Chickens - Tianyu Lei; Liyun Zhuang; Tingting Dai; Qun Niu; Yinli Bao; Weiming Lin; Cuiqin Huang; Xintian Zheng (Veterinary Medicine and Science)
ABSTRACT Background Avian leukosis virus subgroup J (ALV‐J) primarily affects poultry, particularly chickens, leading to tumourigenesis and immunosuppression, which results in substantial economic losses. It is important to note that ALV‐J is commonly found in indigenous chicken breeds in China, and the virus's vertical transmission characteristics present a significant threat to the preservation of local chicken breeds. Objectives The study aimed to investigate the characteristics and effects of the recombinant ALV‐J strain LY2021J, with a focus on its genetic composition and its potential influence on virulence and pathogenicity. Methods LY2021J was isolated using DF‐1 cells and validated by enzyme‐linked immunosorbent assay (ELISA) and IFA. The proviral genome was amplified using segmented PCR and then spliced together using DNASTAR software. Genome‐wide genes, including gag, pol, gp85, and long terminal repeat (LTR), were compared. Recombination sites were analysed using RDP5 and SimPlot software. Pathogenicity was evaluated by monitoring symptoms and conducting examinations on SPF chickens. Results The outbreak of ALV‐J in China has caused significant economic losses in the poultry industry. Although largely controlled in white‐feather broilers and egg‐laying chickens, ALV‐J has spread to yellow‐feather broilers and local breeds. A strain, LY2021J, isolated from Hetian chickens, showed lower mortality despite severe dysplasia. Genetic analysis revealed high similarity between LY2021J and the Chinese strains JS14NT01 and NX0101, suggesting a shared origin. Recombination with strain ev‐1 and specific 3′ UTR deletions may explain LY2021J's reduced virulence. Continued monitoring and prevention strategies are essential to mitigate ALV‐J's impact.